Pictures and words - Stone, Anne.; Australian Film Television & Radio School (North Ryde, NSW. : Australian Film Television & Radio School, 1982)
The video shows how a documentary film is made by mixing and creating an effective marriage of words and pictures
Copy available in DVD format
Keywords: Documentary television programs; Documentary mass media